Analisis kesalahan berbahasa tataran sintaksis pada artikel Inovasi Pembelajaran Bahasa Indonesia Melalui Pendekatan Proses - Naufal Allam Gumelar; Rullyani Kuncoro Putri; Silvia Nita Nur Aryanti; Chafit Ulya (Jurnal Genre (Bahasa, Sastra, dan Pembelajarannya), 2021)
This study aims to explain the form of language error in rhetorical journal entitled "Innovation of Indonesian Language Learning through Process Approach" in syntax level, as well as describe the cause of the error. This research is a descriptive qualitative research. Data collection using techniques in the form of observation of the writings of an article from the journal Rhetoric. Data in the study is divided into two scopes, namely literature research and field research Analysis techniques used include, collecting data in the form of errors in terms of syntax, identifying errors, explaining errors, and evaluating errors. The results of this study are descriptions of the form of language errors include: (1) the unity of ideas, (2) word frugality, (3) logic, and (4) word carefulness.